Juvenile Familial Amyotrophic Lateral Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Four cases of JFALS in a family, with mean age at onset of 15.7 years and exceptionally long survival (mean, 27 years), are reported from the National Institute of Neurology and Neurosurgery, Mexico City.